1D and 2D Zn–Ln coordination polymers based on compartment compounds: [ZnLn(L)(NO3)2(4-ppa)(EtOH)] and [ZnLn(L)(NO3)2(4-pca)(H2O)] (Ln = Eu, Tb; H2 L = 1, 3-bis((3-methoxysalicylidene)amino)propane; 4-Hppa = 4-pyridinepropionic acid; 4-Hpca = 4-pyridinecarboxylic acid). (4th November 2016) - Lee, Ji Hun; Im, Seo Young; Lee, Soon W.
Graphical Abstract: This paper describes the preparation of four 3 d –4 f (3 d  = Zn; 4 f  = Eu, Tb) coordination polymers based on compartment compounds and their emission quenching of the lanthanide ions. Abstract: This paper describes the preparation of four 3 d –4 f (3 d  = Zn; 4 f  = Eu, Tb) coordination polymers and their emission quenching of the lanthanide ions. Two dinuclear Zn–Ln compartment compounds, [ZnLn(L)(NO3 )(CH3 CN)(H2 O)4 ](NO3 )2 (H2 O) (Ln = Eu, Tb), were prepared at room temperature by stirring an acetonitrile solution containing [Zn(L)] (H2  L = 1, 3-bis((3-methoxysalicylidene)amino)propane) and Ln(NO3 )3 · n (H2 O). When these compounds were treated with 4-pyridinepropionic acid (4-Hppa) under microwave-heating conditions, one-dimensional Zn–Ln coordination polymers were formed: [ZnLn(L)(NO3 )2 (4-ppa)(EtOH)] (Ln = Eu (1 ), Tb (2 )). By contrast, these compounds reacted with pyridine-4-carboxylic acid (4-Hpca) to give two-dimensional Zn–Ln coordination polymers: [ZnLn(L)(NO3 )2 (4-pca)(H2 O)] (Ln = Eu (3 ), Tb (4 )). All the compounds (1 –4 ) exhibited the emission quenching of the Ln 3+ ion, probably due to the Ln 3+  → Zn 2+ energy transfer.